Prevalence of pulp therapy in deciduous teeth performed in UNIPÊ Clinical Dentistry School - Fernanda Araújo Trigueiro Campos; Silmara de Andrade Silva; Maria de Fátima Gabínio Siqueira; Isabella Lima Arrais Ribeiro; Ivana Badú de Sousa Olegário (Editorial Ciencias Médicas, 2016)
Introduction: there are several problems that affect children's oral environment, but the main one is caries, due to lack of knowledge, neglect to the child's health, and inadequate information by the parents, the disease progresses and ends up taking larger proportions. Objective: to evaluate the prevalence of pulp therapy in primary teeth performed at the UNIPÊ Clinical School of Dentistry. Methods: we analyzed 600 medical records of children aged 3-10 years treated between the years 2010-2013. The records were analyzed individually seeking data to the main etiologic agents affecting the primary dentition, the identification of the age group in which there is greater prevalence of pulp therapy, which affected teeth most, which techniques of choice according to the material used for vital teeth and devitalized which the pulp and condition. Data were analyzed using descriptive statistics (frequencies and percentages) and inferential. Results: 11 % of the children had at least one tooth that underwent pulp therapy, with a higher prevalence in males with 56.1 %. The main cause was to decay to 95.5 %. The oral hygiene index that prevailed was regular with 56.1 %. The most affected teeth were the first deciduous molar bottom right, with 18.2 % and the second primary molar upper right with 13.6 %. The pulpectomy is most commonly performed treatment, corresponding to 51.5 % of cases. Conclusions: the prevalence of pulp therapy in primary teeth is higher in males and its main etiological factor is decay, the pulpectomy being the main treatment.